2017
DOI: 10.1681/asn.2016101061
|View full text |Cite
|
Sign up to set email alerts
|

Education in Nephrology Fellowship: A Survey-Based Needs Assessment

Abstract: Educational needs assessments for nephrology fellowship training are limited. This study assessed fellows' perceptions of current educational needs and interest in novel modalities that may improve their educational experience and quantified educational resources used by programs and fellows. We distributed a seven-question electronic survey to all United States-based fellows receiving complimentary American Society of Nephrology (ASN) membership at the end of the 2015-2016 academic year in conjunction with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 32 publications
0
56
0
Order By: Relevance
“…Slightly more than 90% rated themselves as competent in placement of femoral dialysis catheters while approximately two‐thirds felt competent in the placement of internal jugular or other dialysis catheters. In a more recent education needs, assessment of fellows in training conducted at the end of the 2015‐2016 academic year, only 10% of 266 respondents indicated that they needed additional training in acute kidney injury diagnosis and management and only 16% indicated a need for additional training in temporary dialysis catheter placement . Specific needs regarding additional training in acute renal replacement therapy were not identified.…”
Section: Assessment Of Training In Acute Renal Replacement Therapymentioning
confidence: 98%
“…Slightly more than 90% rated themselves as competent in placement of femoral dialysis catheters while approximately two‐thirds felt competent in the placement of internal jugular or other dialysis catheters. In a more recent education needs, assessment of fellows in training conducted at the end of the 2015‐2016 academic year, only 10% of 266 respondents indicated that they needed additional training in acute kidney injury diagnosis and management and only 16% indicated a need for additional training in temporary dialysis catheter placement . Specific needs regarding additional training in acute renal replacement therapy were not identified.…”
Section: Assessment Of Training In Acute Renal Replacement Therapymentioning
confidence: 98%
“…Nephrology fellows nationwide have identified that increased training in ultrasonography is a desired element of their curricula . For POCUS to be incorporated into clinical care on a nationwide level, educational curriculum and training programs need to be designed, tested, and integrated into physician training.…”
Section: Pocus Educationmentioning
confidence: 99%
“…POCUS evaluation of joints can identify monosodium urate crystals on cartilage and tophi and can help with diagnostic decision making 47. 5 | POCUS EDUCATIONNephrology fellows nationwide have identified that increased training in ultrasonography is a desired element of their curricula 48. For POCUS to be incorporated into clinical care on a nationwide level, educational curriculum and training programs need to be designed, tested, and integrated into physician training.…”
mentioning
confidence: 99%
“…Although informative, these studies describe perceptions of physicians who have already completed fellowship rather than current fellows. A more recent study from the United States sought to determine current fellows' educational needs and evaluate their interest in potential educational interventions . The percentage of respondents indicating that they were well trained and competent ranged from approximately 80% for in‐center hemodialysis and transplant care to 15% for home hemodialysis care.…”
Section: Gaps In the Education In Nephrologymentioning
confidence: 99%
“…The ABIM and Canadian Internal Medicine regulators require candidates seeking certification in nephrology to be competent in temporary hemodialysis catheter insertion. 5 Traditional nephrology fellowship education may not provide the skills needed to perform this procedure safely with variable education and experience with catheter insertion. In a Canadian study, one-third of trainees felt they were not competent to place a central vein catheter at either the femoral or internal jugular site.…”
Section: Hemodialysis Curriculummentioning
confidence: 99%